Evaluasi Efektifitas Penilaian Kinerja Aplikasi DSS pada Koperasi Simpan Pinjam Keling Kumang - Arief Dwi Hartadi; Oktalia Juwita (Bina Nusantara University, 2013)
Credit union has a substantial role in supporting the growth of the national economy. A number of credit Unions implements DSS application to promote and accelerate the process of decision-making by management. DSS can provide ease of calculation, accuracy in the calculation and examination. However, an ITinvestment in DSS application, as well as other investments, is a segment that depletes costs and effort. The cost is calculated from the procurement, and continues during maintenance or during the investment implemented. Thus the implementation of DSS on a credit union needs to be measured whether it is quite fit and gives positive impacts on decision-making by management and on sale.